Formulation and evaluation of verapamil hydrochloride osmotic controlled release matrix tablets - Vidyadhara, S.; Sasidhar, R. L. C.; Rao, V. Uma Maheswara; Babu, C. H. Showri; Harika, D. Lakshmi (Asian Journal of Pharmaceutics (AJP), 2014)
Osmotically controlled oral drug delivery systems utilize osmotic pressure as energy source for the controlled delivery of drugs, independent of pH and hydrodynamic conditions of gastrointestinal tract (GIT). The present study was aimed to develop osmotic controlled extended release formulations of verapamil hydrochloride an angiotensin II receptor antagonist with anti‑hypertensive activity. Verapamil hydrochloride matrix tablets were prepared by direct compression process using hydroxypropyl methylcellulose (HPMC) K 15M as polymeric material and mannitol as osmogen at varied concentrations. The matrix tablets were further coated with different compositions of ethylcellulose7cps and polyethylene glycol (PEG)‑4000 by pan coating method. Physical parameters such as weight uniformity, drug content, hardness and friability were evaluated for uncoated tablets and were found to be within I. P limits. The coating thickness and percentage of coating applied for various tablets were also evaluated. The optimized coated tablets were further subjected to micro drilling on the upper face to get 0.5 µm orifice diameter. All the tablets were further subjected to dissolution studies by using USP apparatus II with 6.8 pH phosphate buffer as medium. These studies indicated that all the tablets were found to release the drug up to 12 hours, while coated tablets with orifice found to release the drug at zero order rate, which was in good agreement with peppas n > 0.9. Key words: Controlled release, micro drilling, osmotic pressure, verapamil hydrochloride